The smiling mask in service encounters: The impact of surface and deep acting - Sheng Chung Lo; Kai-Ping Huang (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
The purpose of the study was to examine the impact of emotional labor mechanisms (surface acting and deep acting) on service encounters. The literature review has been conducted to examine how two mechanisms impact on employees and customers. The study suggested that as far as employees are concerned, it has been concluded that deep acting rather than surface acting is responsible of high levels of employee satisfaction. The main justification given for this outcome is that employees applying surface acting are not totally able to eradicate the effects of job pressures and demands. Deep acting, however, does not produce such outcome as employees applying this mechanism totally overlook the impact of workplace pressures and demands by placing the interest of the organization first. As far as customers are concerned, the review concluded that surface acting is less likely to result in customer satisfaction. Customer satisfaction with deep acting has been guaranteed. Upon further analysis, it came to the light that surface acting fails to guarantee customer satisfaction since employees using it do not attend to customers with dedication and commitment.
Keywords: L84; M30; 330; Emotional labor; deep acting; surface acting; job satisfaction; customer satisfaction